Study of Zuojin Pill in Treating Chronic Atrophic Gastritis by UPLC-Q-TOF/MS Based on Serum and Urine Metabolomics Combined with Network Pharmacology - Shihua Wu; Xing Chen; Honghong Liu; Ruilin Wang; Jianyu Li; Jianxia Wen; Tao Yang; Ying Wei; Sichen Ren; Shizhang Wei; Manyi Jing; Haotian Li; et al. (International Journal of Analytical Chemistry)
Zuojin Pill (ZJP) is widely used for the treatment of gastrointestinal diseases, while its specific mechanism has not been systematically investigated. The aim of this study was to explore the therapeutic effects and potential mechanism of ZJP in chronic atrophic gastritis (CAG) through UPLC-Q-TOF/MS-based metabolomics combined with network pharmacology. ZJP and omeprazole significantly reduce contents of IL-1β, IL-6, IL-10, and iNOS and improve pathological characteristics. Metabolomic results indicated that the therapeutic effects of ZJP were mainly related to ten metabolites, namely, choline, L-threonine, hydroxypyruvic acid, creatine, taurine, succinic acid, cis-aconitic acid, citric acid, succinic acid semialdehyde, and uric acid. Pathway analysis showed that the treatment of CAG by ZJP was associated with taurine and hypotaurine metabolism; glyoxylate and dicarboxylate metabolism; glycine, serine, and threonine metabolism; glycerophospholipid metabolism; citrate cycle (TCA cycle), alanine, aspartate, and glutamate metabolism; butanoate metabolism; and purine metabolism. Validation of metabolic markers and key targets of network pharmacology through RT-PCR analysis showed that ZJP significantly downregulated a series of inflammatory markers, such as MAPK1, PKIA, RB1, SCN5A, RXRA, E2F1, PTGS1, IGF2, ADRB1, ADRA1B, PTGS2, and GABRA1. This study was the first to use a combination of metabolomics and network pharmacology to clarify the therapeutic effects of ZJP on CAG and the regulation of multiple metabolic pathways.